Law in the bag: il diritto nella borsa del principiante. Per una didattica del diritto democratica e responsabile (Società e diritti, 2020)
Abstract: Starting from an epistemological framework for a teaching of juridical disciplines that is addressed to university students, beginners in the study of law, this paper focuses on the characteristics of a teaching of law that seeks to activate reflection, to encourage participation, to be experiential and democratic. This contribution addresses some reflections for a participatory teaching of law and, in particular, some proposals for the use of cooperative learning methods in the legal education. The underlying hope is that the teaching of law can, especially at this moment, accept the challenge of activating that participatory process of knowledge of the juridical culture and the maturation of an open, responsible and supportive social attitude.
Keywords: Didactics of law; Cooperative learning; Democracy; Responsibility; Common good